2001
DOI: 10.1016/s0042-6989(01)00180-8
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating contrast discontinuities: asymmetries, dipper functions, and perceptual learning

Abstract: In a visual search task, a target has to be found among distractors. For two given elements A and B, the search difficulty can depend on which of the two elements is defined as the target, a phenomenon called search asymmetry. Here, we study to what degree an element's ability to 'win' in a search asymmetry depends on its absolute contrast (first-stage signal) and to what degree it depends on its contrast difference from the background (second-stage signal). One quadrant contained a target texture (2 x 2 Gabor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Although most perceptual learning studies have primarily focused on general learning through practice or training, some studies have identified additional component processes. These include between-session consolidation ( Karni, Tanne, Rubenstein, Askenasy, & Sagi, 1994 ; McDevitt, Rokem, Silver, & Mednick, 2014 ; Sasaki & Watanabe, 2015 ; Stickgold et al., 2002 ; Tamaki, Berard, et al., 2020 ; Tamaki, Wang, Watanabe, & Sasaki, 2019 ; Tamaki, Wang, et al., 2020 ; Yotsumoto et al., 2009 ), offline gain ( Bang et al., 2018 ; Shibata et al., 2017 ), between-session forgetting ( Beard, Levi, & Reich, 1995 ; Mascetti et al., 2013 ), within-session adaptation ( Censor, Karni, & Sagi, 2006 ; Censor, Harris, & Sagi, 2016 ; Sagi, 2011b ), and deterioration ( Dosher & Lu, 2020 ; Zenger-Landolt & Fahle, 2001 ). For example, Yang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Although most perceptual learning studies have primarily focused on general learning through practice or training, some studies have identified additional component processes. These include between-session consolidation ( Karni, Tanne, Rubenstein, Askenasy, & Sagi, 1994 ; McDevitt, Rokem, Silver, & Mednick, 2014 ; Sasaki & Watanabe, 2015 ; Stickgold et al., 2002 ; Tamaki, Berard, et al., 2020 ; Tamaki, Wang, Watanabe, & Sasaki, 2019 ; Tamaki, Wang, et al., 2020 ; Yotsumoto et al., 2009 ), offline gain ( Bang et al., 2018 ; Shibata et al., 2017 ), between-session forgetting ( Beard, Levi, & Reich, 1995 ; Mascetti et al., 2013 ), within-session adaptation ( Censor, Karni, & Sagi, 2006 ; Censor, Harris, & Sagi, 2016 ; Sagi, 2011b ), and deterioration ( Dosher & Lu, 2020 ; Zenger-Landolt & Fahle, 2001 ). For example, Yang et al.…”
Section: Introductionmentioning
confidence: 99%
“…It not only provides a depiction of the time course of learning but also assesses specificity and transfer of learning (see chapter 3 of Dosher & Lu, 2020). It has also been used to evaluate the functional form of learning (e.g., power or exponential function) Dosher & Lu, 2007) and, in some cases, contributions of multiple component processes, such as betweensession improvements due to consolidation (Karni et al, 1994;McDevitt et al, 2014;Sasaki & Watanabe, 2015;Stickgold et al, 2002;Tamaki et al, 2019;Tamaki, Wang, et al, 2020;Yotsumoto et al, 2009) or so-called off-line gain (Bang et al, 2018;Shibata et al, 2017), or alternatively between-session losses due to forgetting (Beard et al, 1995;Mascetti et al, 2013); and/or within-session performance reductions due to processes of adaptation (Censor et al, 2006(Censor et al, , 2016Sagi, 2011a) or general deterioration associated with fatigue or inattention (Dosher & Lu, 2020;Zenger-Landolt & Fahle, 2001).…”
Section: Introductionmentioning
confidence: 99%